Emerging roles for WNK kinases in cancer - Moniz, Sónia (2011)
The subfamily of WNK protein kinases is composed of four human genes and is characterised by a typical sequence variation within the conserved catalytic domain. Although most research has focussed on the role of WNK1, WNK3 and WNK4 in regulating different ion transporters in both the kidney and extrarenal tissues, there is growing evidence for additional roles of WNK kinases in various signalling cascades related to cancer. Here, we review the connection between WNK kinases and tumorigenesis and describe existing experimental evidence as well as potential new links to major aspects of tumour biology. In particular, we discuss their role in G1/S cell cycle progression, metabolic tumour cell adaptation, evasion of apoptosis and metastasis.